Measuring Ambiguity Aversion: A Systematic Experimental Approach - Christian Wilde; Jan Pieter Krahnen; Peter Ockenfels (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2014)
This paper provides a systematic analysis of individual attitudes towards ambiguity, based on laboratory experiments. The design of the analysis allows to capture individual behavior across various levels of ambiguity, ranging from low to high. Attitudes towards risk and attitudes towards ambiguity are disentangled, providing pure measures of ambiguity aversion. Ambiguity aversion is captured in several ways, i.e. as a discount factor net of a risk premium, and as an estimated parameter in a generalized utility function. We find that ambiguity aversion varies across individuals, and with the level of ambiguity, being most prominent for intermediate levels. Around one third of subjects show no aversion, one third show maximum aversion, and one third show intermediate levels of ambiguity aversion, while there is almost no ambiguity seeking. While most theoretical work on ambiguity builds on maxmin expected utility, our results provide evidence that MEU does not adequately capture individual attitudes towards ambiguity for the majority of individuals. Instead, our results support models that allow for intermediate levels of ambiguity aversion. Moreover, we find risk aversion to be statistically unrelated to ambiguity aversion on average. Taken together, the results support the view that ambiguity is an important and distinct argument in decision making under uncertainty.
Keywords: D81; C91; D03; 330